Fatty Acid Profile of Snakehead (Channa striata) and Its By-Product by GC-MS - Nafisah Eka Puteri; Muhammad Irfan Febriansyah (Journal of Nutrition Science, 2023)
The increasing demand for sustainable and high-quality food sources has led to a growing interest in exploring alternative protein options. Fish-derived products, known for their nutritional value, unique flavor profiles, and potential health benefits, have gained significant attention. Among these, snakehead (Channa striata) and its by-products have emerged as promising resources for various food applications, including fish powder production. Fish powder holds immense potential in the food industry as a versatile ingredient, capable of enhancing nutritional content while minimizing waste. This research focuses on investigating the fatty acid composition and volatile compounds present in snakehead fish powder and its by-products. The study employs a combination of analytical techniques, namely gas chromatography-mass spectrometry (GC-MS) and lipid extraction methods, to identify and quantify fatty acids and volatile compounds in the fish powder samples, providing a comprehensive chemical profile. The data reveals variations in the fatty acid composition among different components of the snakehead powder samples, influenced by the fish's feeding habits. The presence of essential fatty acids, including omega-3 and omega-6, highlights the potential health benefits of consuming snakehead powder. Moreover, the identification of odd chain saturated fatty acids (OCS-FAs) in the samples indicates their potential contribution to human health. Notably, snakehead powder contains docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), which have reported preventive effects on human coronary artery disease. In conclusion, snakehead powder is a valuable source of protein and essential fatty acids, with potential implications for human health. The study emphasizes the significance of incorporating polyunsaturated fatty acids (PUFAs) into the human diet, potentially through fish powder consumption. Overall, the findings highlight the potential benefits of snakehead meat, head, skin, and bone, encouraging the development of functional food products and their potential use in preventing stunting.